Amplification and analysis of specific DNA and RNA sequences of bovine leukemia virus from infected cows by polymerase chain reaction. - Sherman, M P (1992)
Bovine leukemia virus (BLV) is the etiologic agent of leukemia in cattle and is believed to cause decreases in milk productivity, fertility, and life span in infected cows. BLV is a type C retrovirus in the Oncovirinae subfamily. It is most closely related to human T-cell lymphoma/leukemia virus type I (HTLV-I) and type II (HTLV-II). Since the polymerase chain reaction (PCR) provides rapid and efficient amplification of DNA sequences, primers were designed to amplify regions of the polymerase (pol) and pX genes specific for BLV targets. These sets of primers consistently amplified as few as 10 copies of BLV DNA contained in a plasmid in the background of 1 microgram of either human or bovine chromosomal DNA. In addition, no amplification products were detected from cell lines infected with HTLV-I, HTLV-II, or human immunodeficiency virus type 1 or 2 by the BLV PCR systems. Samples of peripheral blood mononuclear cells from 18 cows, previously determined to be serologically positive or negative, were correctly identified in a blind study as containing proviral DNA by use of the BLV primers and probes. Cloning and sequencing of amplified products revealed finite sequence variations among a previously cloned BLV isolate, the wild-type virus, and the published genome. Reverse transcriptase-directed PCR with the primers for both BLV pol and BLV pX was performed on plasma from a BLV-infected cow and detected in vivo BLV RNA expression. In summary, we have developed a specific and sensitive assay using PCR for the detection and identification of BLV infections; this assay can now be applied to clinical and basic research questions in veterinary medicine.